PARTISIPASI WAHDAH ISLAMIYAH DALAM PEMBANGUNAN KOTA MAKASSAR PERSPEKTIF SIYASAH SYAR’IYYAH - Hasan, Nun Ainun; Mustafa, Adriana (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The development of Islamic organizations in Indonesia is so massive, the formation of various Islamic organizations provides awareness of the social and political power of the renewal movement. The existence of Wahdah Islamiyah as an Islamic organization and movement that chose the wasathiyah (middle / moderate) path transformed into a more contextual movement in adapting to the conditions and culture of society. This study aims to find out how Wahdah Islamiyah's participation in the development of Makassar City using qualitative research methods. The results showed that Wahdah Islamiyah's real contribution in the development of Makassar City focused on the fields of education, health, and socio-community.